Systematizing destigmatization in the context of media and communication: a systematic literature review - Kunze, Deborah (Frontiers in Communication, 2024)
Destigmatization is a crucial step toward achieving societal equality. Media contribute both to the stigmatization and destigmatization of various groups. Through a systematic literature review, the present study aims to develop a comprehensive overview of destigmatization in the context of media and communication. A final sample of 79 scientific publications was analyzed and synthesized. First, a systematically derived, interdisciplinary applicable definition of destigmatization is presented. Second, an overview of factors influencing destigmatization is given, categorized into four factor groups: contact, education, language and terminology, and framing. Third, the processual character of destigmatization, referring to reflexive and rule-based processes, is discussed. This systematic literature review emphasizes the responsibility and potential positive impact of media and communication for destigmatization. The findings provide a basis for adaptation and expansion by future research focusing on various stigmatized groups and settings.